Perbedaan perilaku agresi antara siswa laki-laki dan siswa perempuan di SMPN 1 Kasreman Ngawi - Arih Merdekasari; Moh Toriqul Chaer (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
This study aims to examine differences in aggressive behavior among male students and female students at the Junior High School 1 Kasreman. The method of research is a scientific activity carried out in stages to achieve research objectives. The research used is descriptive survey research. The study population is students aged 12-15 years (early adolescent phase) at the Junior High School 1 Kasreman. The sampling technique used purposive random sampling technique. Characteristics of the study sample are students aged 12-15 years in junior high school 1 Kasreman as many as 104 students. A statistical significance level of the test uses the hypothesis test in both directions. Hypothesis test shows the value of aggressive behavior (sig = 0.018), it can be seen that the p-value of <0.05, so it can be concluded that hypothesis was accepted. There are differences in the level of aggressive behavior among girls and boys.